ACTION RESEARCH : An Easy Guide for Researchers - Sarala Thulasi Palpanadan (2020)
Action research is a reflective strategy that can be used by researchers for solving workplace issues in the real life settings. Researchers are able to explore various issues and plan for the change by conducting action research that ensures their continuous professional growth.The publication of this guidebook aims to introduce researchers not only to the models of action research but also to assist them to develop, implement, evaluate, and publish action research projects in their respective fields.It is hoped that this guidebook will be highly helpful and beneficial to the researchers from all walks of life. The guidebook will meet the needs of those who would like to embark on action research projects in various fields especially in the educational contexts. Thus, this book can be very useful for anyone who wishes to conduct action research, be it on a smaller scale or bigger scale study. This book highlights not only the ways of conducting action research effectively but also alerts researchers about the possible challenges that might hinder the flow of the research. Hence, this book should be kept with researchers for quick reference all the time.